Vocabulary development in a grade 7 class using dictionary skills: an action research project - Wells, Stephanie Alice (Rhodes University, Faculty of Education, Department of Education, 2011)
As I was involved as a voluntary, part-time teacher in a local, semi-rural school in the Eastern Cape, South Africa, I became increasingly aware of the learners' lack of English literacy. I therefore decided to do a practical research on vocabulary development, focusing on dictionary skills. In this thesis I describe how I implemented a vocabulary development programme as an Action Research project. My research group was a grade 7 class of English First Additional Language learners who had minimal exposure to English at school and in their communities. The class was a mixture of Afrikaans and isiXhosa home language speakers and the medium of instruction was Afrikaans. The school served a low-income community and was poorly resourced. As dictionary skills is a requirement of the national curriculum, I used 10 time-tabled lessons over a 5 week period to introduce the learners to dictionaries. My data sources were a journal detailing my reflections on each lesson; a video-recording of the lessons; small group interviews after each lesson which were audio-recorded; tasksheets on the work covered in class and questionnaires asking the learners for written responses to the lessons. The class teacher who filmed the lessons was also asked for feedback during and after the programme. My goals were to assess my teaching approach in these circumstances and to what extent the outcomes were positive for the learners. As I had come from a background of English Home Language teaching in good, well-resourced schools I found I had to question many of my assumptions. Although I was an experienced, qualified and confident teacher, I was continually having to reassess my teaching methods which were being challenged by very different classroom conditions. The outcomes of the research show why I was not able to achieve what I had thought I could in the time given.
Keywords: English language -- Study and teaching (Elementary) -- South Africa -- Eastern Cape; Vocabulary -- Study and teaching (Elementary) -- South Africa -- Eastern Cape; English language Dictionaries -- Polyglot -- Study and teaching (Elementary) -- South Africa -- Eastern Cape